Research on Flood Propagation for Different Dam Failure Modes: A Case Study in Shenzhen, China - Wang, Weiqi; Chen, Wenjie; Huang, Guoru (Frontiers in Earth Science, 2020)
Dam-break flood simulation can evaluate the impact of a dam-break, and is significant in conducting risk analyses, creating emergency plans, and mitigating calamities. This study investigates the dam-break flood propagation in the downstream urban areas of the Minzhi Reservoir in Shenzhen, China, based on a two-dimension shallow-water model (SWM-2D). The SWM-2D solves two-dimensional shallow water equations for free surface flow using the finite-volume method. A refined grid with an unstructured mesh of triangular cells, constrained by building walls, is constructed to represent urban structures in this model. The flood hydrographs of dam-break and the flood propagation under different failure modes are calculated by adopting two breach mechanisms, namely instantaneous dam-break and gradual dam-break. The results indicate that the peak flow of the instantaneous dam-break is relatively large at the beginning of the dam-break. The gradual dam-break peak flow is relatively small when seepage failure deformation develops towards the upper part of the dam. The inundation information during the evolution of the dam-break flood, including the regularity of the flood propagation, distribution of maximum water depth, and variation of depth and velocity with time are also analysed.